PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS LANGUAGE LEARNING AS A MEANS OF COMMUNICATION (Pedagogy of Higher and Secondary Education, 2007)
The article investigates psychological and pedagogical conditions of learning a language as means of communication.